The Urgency of Android-Based Interactive Multimedia Development to Improve High School Students Collaboration Skills - Pramusita, Mutiara Kusuma Ananda; Sariyatun; Suryono, Hassan (Journal of Education Technology, 2024)
Humans as social creatures are defined as humans who cannot live alone so they work together to build a harmonious social life with collaboration skills. Through the application of education, collaboration skills are one of the skills of the 21st century. In applying sociology learning, students have difficulty understanding sociology material and developing their collaboration skills. Even though collaboration skills are needed for social life. Based on the problems above, this research aims to develop Android-based interactive multimedia to optimize mobile learning on social interaction material. This research is a type of development research (R&D) using the ADDIE model which involves media experts, content experts, and experts on skills measurement instruments in learning. The data collection technique uses a quantitative descriptive approach with percentage analysis. The results of data analysis show that 2 media experts gave an average score of 3.71 with a percentage of 93% percent. Then 4 learning content experts gave an average score of 3.9 with a percentage of 97.50%, and finally, 4 learning instrument experts gave an average score of 4 with a percentage of 100%. It was concluded that interactive multimedia was declared very suitable for use in teaching sociology for class X SMA/MA. The Android-based interactive multimedia being developed is expected to contribute to the urgent need for learning media innovation that is adapted to the learning needs of the 21st Century.